2015
DOI: 10.1002/jrs.4754
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic characteristics of diallyl trisulfide acting on trans‐crotonaldehyde

Abstract: In this paper, the molecular mechanism of diallyl trisulfide (DATS) on trans-crotonaldehyde (TCA) was studied by UV-vis absorption and Raman spectroscopies combining with density functional theory calculations. Experimental results indicate that the introduction of DATS can not only make the maximum absorption peak of TCA shift 15 nm, but also obviously alter the Raman vibrational frequency of aldehyde (-CHO). In addition, the Raman intensity of TCA decreased significantly, especially in the presence of mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Su and co‐workers monitored the liquid phase concentration in a polymorphic system by Raman spectroscopy. Their optimized model was subsequently applied to predict the liquid phase concentration in a multiphase multicomponent dynamic process, the solvent mediated polymorphic transformation of mannitol, and it was shown that the offline measurements and the predicted values were mainly in agreement with one another . Upadhyay et al .…”
Section: Liquids Solutions and Liquid Interactionsmentioning
confidence: 81%
See 1 more Smart Citation
“…Su and co‐workers monitored the liquid phase concentration in a polymorphic system by Raman spectroscopy. Their optimized model was subsequently applied to predict the liquid phase concentration in a multiphase multicomponent dynamic process, the solvent mediated polymorphic transformation of mannitol, and it was shown that the offline measurements and the predicted values were mainly in agreement with one another . Upadhyay et al .…”
Section: Liquids Solutions and Liquid Interactionsmentioning
confidence: 81%
“…Their optimized model was subsequently applied to predict the liquid phase concentration in a multiphase multicomponent dynamic process, the solvent mediated polymorphic transformation of mannitol, and it was shown that the offline measurements and the predicted values were mainly in agreement with one another. [146] Upadhyay et al carried out vibrational studies of polar aprotic molecules in aromatic chemical and isotropic solvents as a combined experimental and quantum chemical investigation. Theoretical calculations were compared with the experimental findings and good agreement of the results were obtained.…”
Section: Liquids Solutions and Liquid Interactionsmentioning
confidence: 99%
“…Using ethanol as solvent, the maximum UV‐vis peak of TCA (12.5 mM) was located at 316 nm (Fig. , black line) , and the maximum UV‐vis main peak and shoulder peak of Res (0.01 mM) were situated at 305 and 320 nm (Fig. , blue line) , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The buffer was kept cold at 4 °C during the experiment. Other procedures of mitochondrial preparation were operated according to the previous method without modification . Mitochondrial samples were used within 1 h.…”
Section: Methodsmentioning
confidence: 99%
“…All calculations were performed using density function theory (DFT) methods implemented in the Gaussian 09 package, with the hybrid functional CAM-B3LYP , and the basis set 6-31+G­(d,p). , The reliability of this functional has been validated in our prior study by comparing the excitation energies of two equilibrium states of the TDHY–fluorene molecule with reported higher levels of calculation using TD-BH&HLYP/6-31G­(d) and SA-REBH&HLYP/6-31G­(d) functionals.…”
Section: Computational Detailsmentioning
confidence: 99%